2023
DOI: 10.3390/jcm12041576
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing and Treating Infertility via Transvaginal Natural Orifice Transluminal Endoscopic Surgery versus Laparoendoscopic Single-Site Surgery: A Retrospective Study

Abstract: Objective: To evaluate the efficacy and safety of transvaginal natural orifice transluminal endoscopic surgery (vNOTES) in the treatment of female infertility. Materials and methods: This study includes 174 female patients with a history of long-standing female infertility. We retrospectively reviewed 41 patients who underwent hysterolaparoscopy (HL) via transvaginal natural orifice transluminal endoscopic surgery (vNOTES) and 133 patients who underwent laparoendoscopic single-site surgery (LESS). Demographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…vNOTES appears to be associated with reduced blood loss, shorter operative time, less postoperative pain, and better cosmetic results. [1][2][3] Despite these promising results, little is known about the impact of vNOTES adnexal surgery on women's sexual quality of life and the risk of developing postoperative dyspareunia. 4 During vNOTES adnexal procedures, access to the peritoneal cavity is achieved with an Alexis vaginal retractor inserted into the Douglas pouch through a posterior colpotomy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…vNOTES appears to be associated with reduced blood loss, shorter operative time, less postoperative pain, and better cosmetic results. [1][2][3] Despite these promising results, little is known about the impact of vNOTES adnexal surgery on women's sexual quality of life and the risk of developing postoperative dyspareunia. 4 During vNOTES adnexal procedures, access to the peritoneal cavity is achieved with an Alexis vaginal retractor inserted into the Douglas pouch through a posterior colpotomy.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, vNOTES has increasingly been used for adnexal procedures, generally showing better perioperative outcomes when compared to CL and LESS. vNOTES appears to be associated with reduced blood loss, shorter operative time, less postoperative pain, and better cosmetic results 1–3 . Despite these promising results, little is known about the impact of vNOTES adnexal surgery on women's sexual quality of life and the risk of developing postoperative dyspareunia 4 …”
Section: Introductionmentioning
confidence: 99%
“…Infertility is a human disease of the male and female reproductive systems, and according to the World Health Organization (WHO), infertility affects around 15% of couples of reproductive age [1]. The American Society for Reproductive Medicine defines infertility as being characterized by the inability to conceive after having unvarying and unguarded vaginal sex for a minimum of 365 days in a year [2], which affects around 48.5 million couples globally [3]; however, it varies by ethnic region and 8-12% is an estimation of the infertility among reproductive-aged couples [4]. Pelvic adhesions, endometriosis, ovulatory disorders, hyperprolactinemia and tubal anomalies are considered the female factors and account for 35% of infertility cases, while male factors are responsible for 30% and 20% is based on a combination of factors from both the genders.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, minimally invasive surgery (MIS) has become one of the leading advanced therapeutic technology in the management of patients with various types of benign diseases, not only due to successful transformation of the treatment landscape but also clear demonstration of many advantages, such as small wound, better cosmetics, less wound pain, sooner recovery, and easy fulfillments of enhanced recovery after surgery (ERAS) programs compared to conventional exploratory laparotomic approach. 1–6 However, for the management of patients with malignant tumors, there are many debated issues and controversies, although many studies have confirmed that MIS can be successfully in place of traditional exploratory laparotomy in the management of many kinds of malignancies, based on the validated effectiveness and safety of MIS. 7–12 Among the aforementioned cancers, the gynecological organ-related cancers may be one of highly debated issues, because the preferred surgical therapy for endometrioid-type endometrial cancer (E-EC) is an MIS (laparoscopic surgery or robotic surgery) and the choice of treatment for epithelial ovarian cancer (EOC) is a standard midline incision-based exploratory laparotomy.…”
mentioning
confidence: 99%